2016
DOI: 10.3390/w8020055
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Selecting Best Management Practices Integrating Multiple Stakeholders and Criteria. Part 1: Methodology

Abstract: Abstract:The implementation of stormwater Best Management Practices (BMPs) could help re-establish the natural hydrological cycle of watersheds after urbanization, with each BMP presenting a different performance across a range of criteria (flood prevention, pollutant removal, etc.). Additionally, conflicting views from the relevant stakeholders may arise, resulting in a complex selection process. This paper proposes a methodology for BMP selection based on the application of multi-criteria decision aid (MCDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…An analytical hierarchy process (AHP) and an analytical network process (ANP) are used to determine the weights for disaster potential for disaster-resistant communities on hillsides. e ANP, which is an extension of the AHP, adds feedback to the AHP to predict the internal relationships between all criteria, objectives, and projects using ratio scales, to allow robust decision-making processes [2,[17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…An analytical hierarchy process (AHP) and an analytical network process (ANP) are used to determine the weights for disaster potential for disaster-resistant communities on hillsides. e ANP, which is an extension of the AHP, adds feedback to the AHP to predict the internal relationships between all criteria, objectives, and projects using ratio scales, to allow robust decision-making processes [2,[17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…However, citizens are usually more sensitive in this case. Engineers, municipal governments and developers are somewhere between two these groups [9]. Stakeholders' opinion about TP removal is very similar to TN removal [9].…”
Section: Stormwater Quantity Functionmentioning
confidence: 99%
“…ELECTRE dominant concordance matrix obtained from threshold of 0.73 that calculated by using equation (15). The equation ( 16) is used to find the dominant discordance matrix as in Table 13.…”
Section: Electre Dominant Discordance Matrixmentioning
confidence: 99%
“…While research on TOPSIS sensitivity is found in studies [13][14] which change the weight of one attributes to determine the level of TOPSIS sensitivity. In [15][16] showed the level of validity generated by ELECTRE.…”
Section: Introductionmentioning
confidence: 99%